2004
DOI: 10.1073/pnas.0308571101
|View full text |Cite
|
Sign up to set email alerts
|

A DNA polymerase β mutant from colon cancer cells induces mutations

Abstract: Previous investigations have shown that Ϸ35% of the 90 tumors analyzed to date contain mutations within the DNA polymerase ␤ (pol ␤) gene. The existence of pol ␤ mutations in a substantial fraction of human tumors studied suggests a link between DNA pol ␤ and cancer. A DNA pol ␤ variant, in which Lys-289 has been altered to Met, was identified previously in a colorectal carcinoma. The K289M protein was expressed in mouse L cells containing the cII mutational target. The DNA was packaged and used to infect bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 39 publications
4
127
1
Order By: Relevance
“…[15][16][17] In support of this idea we demonstrated that both I260M and K289M are sequence-specific mutator mutants. 13,12 Because Pol β functions in BER, our results suggest that K289M and I260M are deficient in discriminating between the correct and incorrect dNTP as they fill the gap after excision of the damaged base. If mistakes are introduced into key growth control genes during gap filling, they could result in mutations that lead to cancer.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 91%
See 1 more Smart Citation
“…[15][16][17] In support of this idea we demonstrated that both I260M and K289M are sequence-specific mutator mutants. 13,12 Because Pol β functions in BER, our results suggest that K289M and I260M are deficient in discriminating between the correct and incorrect dNTP as they fill the gap after excision of the damaged base. If mistakes are introduced into key growth control genes during gap filling, they could result in mutations that lead to cancer.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 91%
“…[11][12][13] Specifically, expression of either the K289M colon or I260M prostate cancer Pol β variant in mouse fibroblasts, in the presence of endogenous wild-type Pol β, results in cellular transformation as assessed by focus formation and anchorage independent growth. [11][12][13] A mutagenic basis for the transforming activity of the Pol β variants is suggested by the findings that different clones of cells expressing these polymerases were not immediately transformed but acquired the transformed phenotype after a variable number of passages and that the transformed phenotype persisted even after the expression of the Pol β variant was extinguished. The latter finding indicates that the Pol β variants induce transformation by a "hit-and-run" mechanism in which the continued expression of the initiating event is not required to maintain the transformed state.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 99%
“…I260M induces expansions of TC repeats within a run of TCs, frameshift mutations within dipyrimidine sequences, and base substitutions within sequence contexts in which WT pol ␤ does not induce mutations (S.D., K. Eckert, and J.B.S., unpublished data). The K289M variant induces transversions within interrupted runs of like residues at frequencies that are much greater than those of the WT protein (24). The molecular basis of mutation induction by the I260M and K289M proteins appears to be altered positioning of the DNA within the active site of each of these enzymes as compared with WT pol ␤.…”
Section: Mutagenic Properties Of the Pol ␤ Variants Could Play An Impmentioning
confidence: 95%
“…We have shown that K289M variant protein induces cellular transformation in immortalized mouse epithelial cells by increasing the mutation frequency of the cells (22,23). We have also shown that this variant is a sequence context-dependent mutator, in that it induces mutations at a frequency 16 times higher than wild-type (WT) pol ␤ within a nucleotide sequence context found in the adenomatous polyposis coli gene that is frequently mutated in colon cancer (22,24).…”
mentioning
confidence: 99%